Smoking Status Predicts Preoperative Opioid Use in a Dose-dependent Pattern Amongst Geriatric Female Spine Surgical Patients. (16th November 2020) - Christian, Zachary; Youssef, Carl A; Aoun, Salah G; Afuwape, Olusoji A; Hall, Kristen; Adeyemo, Emmanuel; Barrie, Umaru; Dosselman, Luke; Pernik, Mark N; Reyes, Valery P; Morrill, Kevin C; Bagley, Carlos A
Abstract: INTRODUCTION: Smoking status and opioid medication intake have been associated with increased opioid consumption and suboptimal functional outcomes after spine surgery. However, the interaction between smoking and preoperative opioid intake has not been studied in the elderly. METHODS: The records of 536 consecutive patients aged more than 65 years who underwent elective spinal surgery between November 2014 and August 2017 at a single institution were reviewed. Data was collected prospectively in a spine registry and included demographic information, smoking status, and procedural details. Primary outcomes included rates of preoperative opioid consumption and postoperative hospital length of stay and complications. RESULTS: Males were more likely to be smokers than females (45.70% vs 32.91%; P  < .001), whereas females were more likely to take opioid analgesics preoperatively (49.15% vs 40.40%; P  = .022). Women with a history of smoking were more likely to have increased preoperative opioid consumption compared to those with no history of smoking (63.64% vs. 42.04%; P  < .001). Such a relationship was not found in men. Subgroups analysis of female patients with a history of tobacco use comparing current and former smoker status, showed that both groups exhibited increased preoperative opioid consumption compared to patients who never smoked (88.89% vs 42.04%; P  < .001 for current users; 59.42% vs 42.04% for former users; P  = .008). There was also a dose-depended relationship between smoking and increased preoperative opioid consumption. No differences in average length of stay or direct postoperative complications were observed between patients with a history of tobacco use and nonusers and between patients taking opioid medication preoperatively and those who were opioid-naïve in this cohort. CONCLUSION: Geriatric female spine patients with a history of smoking have a higher incidence of preoperative opioid consumption. Opioid intake appears to increase with the number of pack-years in patients with a history of smoking or who currently smoke. These findings highlight the importance of smoking cessation in older spine candidates, especially women, as it may encourage a decrease in opioid consumption even outside of the operative setting.